Surface layer carbonized conductive polymer composite electrode and preparation method thereof

By super-fast carbonization treatment on the surface of the conductive polymer, a composite electrode with a core (conductive polymer)-shell (conductive hard shell) structure is formed, which solves the stability problem caused by volume changes in the conductive polymer during cyclic charging and discharging, improves the structural stability and conductivity of the electrode material, and improves the performance and application prospects of supercapacitors.

CN119724948APending Publication Date: 2025-03-28QINGHAI HUANGHE HYDROPOWER DEVELOPMENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311256668.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The volume expansion-contraction of the conductive polymer during cyclic charging and discharge leads to rupture of the electrode material and loss of conductivity, and the electron transfer is limited, limiting the rate performance and power density of the supercapacitor.

Method used

By performing ultra-fast carbonization on the surface of the conductive polymer material, a composite electrode with a core (conductive polymer)-shell (conductive hard shell) structure is formed, which suppresses volume changes and improves the electron transport path.

Benefits of technology

Effectively improve the structural stability and conductivity of conductive polymer electrode materials, improve the cyclic stability and rate performance of supercapacitors, and reduce costs and process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724948A_ABST
    Figure CN119724948A_ABST
Patent Text Reader

Abstract

The invention relates to a surface-carbonized conductive polymer composite electrode and a preparation method thereof, and belongs to the technical field of capacitor electrode material preparation. The preparation method comprises the following steps: immersing an oxidized substrate carbon material into a monomer solution of a conductive polymer, stirring, dropwise adding a reaction accelerator solution at 0-5 DEG C, carrying out an oxidative polymerization reaction, and washing and drying after the oxidative polymerization reaction is completed to obtain a substrate-coated conductive polymer; and carrying out carbonization treatment on the obtained substrate wrapped conductive polymer in an inert atmosphere, and obtaining the surface layer carbonized conductive polymer composite electrode after the carbonization treatment is completed. The surface layer of the conductive polymer material is rapidly and uniformly carbonized at a high temperature through an ultra-rapid carbonization treatment process to form the core-shell structure composite electrode, and the structure can effectively inhibit volume expansion and shrinkage of the conductive polymer in the cyclic charging and discharging process and is beneficial to improving the structural stability of the conductive polymer electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of capacitor electrode material preparation, and particularly relates to a surface carbonized conductive polymer composite electrode and a preparation method thereof. Background Art

[0002] Supercapacitors are a new type of energy storage device that combines high power density, high energy density, high reliability and long cycle life. They just make up for the electrochemical performance gap between batteries and electrostatic capacitors, and have extremely broad application prospects in portable consumer electronic devices, electric vehicles, cranes, emergency system equipment and large-scale energy storage. The electrochemical performance of supercapacitors depends largely on the type and microstructure of the electrode material used. Among various supercapacitor electrode materials, conductive polymers (including polyaniline (PANI), polypyrrole (PPY) and polythiophene (PTH)) are regarded as electrode materials with great development prospects due to their high theoretical specific capacitance, low price, environmental friendliness and easy synthesis. However, the insertion-extraction behavior of ions in conductive polymers during the cyclic charge and discharge process will cause the conductive polymers to expand and contract repeatedly. The severe volume change will eventually cause the electrode material to rupture and fall off, causing the electrode material to lose its conductivity and charge storage capacity, resulting in poor cycle stability. In addition, the low conductivity of conductive polymers severely limits the rapid transmission of electrons inside them, resulting in limited rate performance and power density of supercapacitors based on conductive polymer electrode materials.

[0003] In order to give full play to the potential of conductive polymer materials in supercapacitors and overcome their shortcomings, they can be compounded with hard shell materials with excellent mechanical properties and conductivity, and their structural stability and conductivity can be improved by suppressing the volume effect of conductive polymers and providing effective electron transfer paths. A large number of research results show that by coating the surface of conductive polymer materials with hard shell materials such as RuO2, graphene, and hydrothermal carbon to form a core (conductive polymer)-shell (conductive hard shell) structure composite electrode material, the electrochemical stability of conductive polymers can be effectively improved. The literature "C. Xia, W. Chen, X. Wang et al. Highly stable supercapacitors with conducting polymer core-shell electrodes for energy storage applications, Advanced Energy Materials, 2015, 5 (8)" uses atomic layer deposition (ALD) to introduce nano-RuO2 to the surface of PANI to improve the cycle stability and electrochemical performance of PANI. The prepared PANI / RuO2 composite electrode can still retain a capacity of up to 88% after 10,000 cycles of charge and discharge. However, the ALD process and the high price of precious metals such as RuO2 limit the large-scale application of this method. The document "T.Liu, L.Finn, M.Yu et al.Polyaniline and polypyrrole pseudocapacitor electrodes with excellent cycling stability, Nano letters, 2014, 14 (5): 2522-2527" reported a method of wrapping a carbon shell on the surface of a conductive polymer through a hydrothermal reaction of a glucose solution. The prepared conductive polymer @ C composite electrode can still maintain a capacity of ~90% after 10,000 cycles. However, the long time taken for the hydrothermal reaction and the insufficient conductivity of the hydrothermal carbon shell generated at a lower temperature limit the practicality of this method. Summary of the invention

[0004] In view of the above problems, the present invention provides a surface carbonized conductive polymer composite electrode and a preparation method thereof.

[0005] The first object of the present invention is achieved by the following technical solutions:

[0006] A method for preparing a surface carbonized conductive polymer composite electrode, comprising:

[0007] The oxidized carbon material is immersed in a monomer solution of a conductive polymer, stirred, and then a reaction accelerator solution is added dropwise at 0 to 5° C. to perform an oxidative polymerization reaction, and after the oxidative polymerization reaction is completed, the oxidized carbon material is washed and dried to obtain a conductive polymer wrapped on the substrate;

[0008] The obtained substrate wrapped with the conductive polymer is carbonized in an inert atmosphere. After the carbonization is completed, a surface carbonized conductive polymer composite electrode is obtained.

[0009] Furthermore, the base carbon material includes one of carbon fiber, carbon cloth and graphite paper.

[0010] Furthermore, the oxidation treatment condition is 350-450° C. for 1-2 hours in an air atmosphere.

[0011] Furthermore, the conductive polymer is one of polyaniline, polypyrrole and polythiophene.

[0012] Furthermore, the conductive polymer is polyaniline, the monomer solution of the conductive polymer is aniline hydrochloride solution, and the reaction accelerator solution is ammonium persulfate hydrochloride solution.

[0013] Furthermore, the conductive polymer is polypyrrole, the monomer solution of the conductive polymer is a hydrochloric acid solution of pyrrole monomer, and the reaction accelerator solution is a hydrochloric acid ammonium persulfate solution; the conductive polymer is polyethylene dioxythiophene, the monomer solution of the conductive polymer is an ether solution of 3,4-ethylene dioxythiophene, and the reaction accelerator solution is an ether solution of ammonium persulfate, wherein the ether solution of 3,4-ethylene dioxythiophene contains ferric chloride.

[0014] Furthermore, the carbonization process (ultra-fast carbonization process) is specifically performed as follows:

[0015] The obtained substrate wrapped with the conductive polymer is placed at the upwind port of a tube furnace 0 to 15 cm away from the heating area;

[0016] In an inert atmosphere, the heating zone of the tube furnace is heated to 900-1200°C at 1-10°C / s;

[0017] At the same time, the substrate-wrapped conductive polymer is moved to the heating area within 0 to 5 seconds and carbonized for 5 to 60 seconds;

[0018] Subsequently, the substrate-wrapped conductive polymer is removed from the heating area within 0 to 5 seconds to complete the carbonization treatment, and then cooled in the furnace to obtain a surface carbonized conductive polymer composite electrode.

[0019] Furthermore, the movement of the substrate-wrapped conductive polymer in the tube furnace is achieved by a sample delivery rod;

[0020] The sample delivery rod is movably connected to the tubular furnace, and an airtight structure is provided at the connection between the sample delivery rod and the tubular furnace;

[0021] One end of the sample delivery rod is placed in the tube furnace, and the other end of the sample delivery rod is located outside the tube furnace.

[0022] Furthermore, the airtight structure is an O-ring or a metal seal.

[0023] The second object of the present invention is achieved by the following technical solutions:

[0024] A surface carbonized conductive polymer composite electrode is made by the above-mentioned preparation method, comprising a carbon material substrate, a conductive polymer wrapped on the surface of the carbon material substrate and a carbide on the surface of the conductive polymer.

[0025] Beneficial effects of the present invention:

[0026] (1) The present invention uses an ultra-fast carbonization process to quickly and uniformly carbonize the surface layer (within 100 nm) of the conductive polymer material at high temperature to form a core (conductive polymer)-shell (conductive hard shell) structure composite electrode. This structure can effectively inhibit the volume expansion and contraction of the conductive polymer during the cyclic charge and discharge process, which is beneficial to improving the structural stability of the conductive polymer electrode material;

[0027] (2) This process forms a stable organic-carbon heterogeneous interface by in-situ carbonization of the surface of the conductive polymer material, thereby solving the problems of loose bonding between the "core" and the "shell" of the core (conductive polymer)-shell (conductive hard shell) structure composite electrode made by the prior art and the insignificant improvement in the electrode cycle stability;

[0028] (3) Since the molecular structure of the conductive polymer contains a certain amount of nitrogen atoms, the carbon material obtained by its conversion at high temperature will also be doped with a small amount of nitrogen-containing functional groups. The presence of nitrogen-containing functional groups is conducive to the improvement of the conductive properties of the carbon material; at the same time, the close combination between the nitrogen-doped carbon shell and the conductive polymer substrate also makes the charge transfer on the heterogeneous interface more efficient;

[0029] (4) The present invention uses a high-temperature ultra-fast carbonization method to treat conductive polymers. Compared with coating nano-RuO2 shells and hydrothermal carbon shells, the process has a short cycle, low energy consumption, low cost and is easy to industrialize;

[0030] (5) The core (conductive polymer)-shell (conductive hard shell) structure composite electrode prepared by the present invention effectively solves the volume effect problem that limits the practical application of conductive polymer electrode materials while combining the characteristics of conductive polymer and carbon materials. It can have good application prospects and economy in the field of supercapacitors and other energy storage device electrode materials.

[0031] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 A flow chart showing a method for preparing a surface carbonized conductive polymer composite electrode according to an embodiment of the present invention;

[0034] Figure 2 The SEM image of the substrate-wrapped conductive polyaniline in Example 1 of the present invention is shown;

[0035] Figure 3 The TEM image of the substrate-wrapped conductive polyaniline according to Example 1 of the present invention is shown;

[0036] Figure 4 The SEM image of the surface carbonized conductive polymer composite electrode according to Example 1 of the present invention is shown;

[0037] Figure 5 The HRTEM image of the surface carbonized conductive polymer composite electrode in Example 1 of the present invention is shown;

[0038] Figure 6 The rate curve of the composite electrode of substrate-wrapped conductive polyaniline and surface-carbonized conductive polymer in Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] like Figure 1 As shown, a method for preparing a surface carbonized conductive polymer composite electrode according to an embodiment of the present invention comprises:

[0041] Step 1, immersing the oxidized carbon material in a monomer solution of a conductive polymer, stirring, then dropping a reaction accelerator solution at 0-5°C to carry out an oxidative polymerization reaction, washing and drying after the oxidative polymerization reaction is completed, to obtain a substrate-wrapped conductive polymer;

[0042] Step 2: Carry out carbonization treatment on the obtained substrate wrapped with the conductive polymer in an inert atmosphere. After the carbonization treatment is completed, a surface carbonized conductive polymer composite electrode is obtained.

[0043] In the embodiment of the present invention, the base carbon material is an electrode material well known to those skilled in the art, such as carbon fiber, carbon cloth, graphite paper, etc. The present invention does not limit the base carbon material.

[0044] In the embodiment of the present invention, the oxidation treatment condition is 350-450° C. in air atmosphere for 1-2 hours;

[0045] Specifically, the oxidation treatment condition may be 350° C. in an air atmosphere for 1 to 2 hours; the oxidation treatment condition may be 360° C. in an air atmosphere for 1 to 2 hours; the oxidation treatment condition may be 370° C. in an air atmosphere for 1 to 2 hours; the oxidation treatment condition may be 380° C. in an air atmosphere for 1 to 2 hours; the oxidation treatment condition may also be 390° C. in an air atmosphere for 1 to 2 hours; the oxidation treatment condition may also be 400° C. in an air atmosphere for 1 to 2 hours; the oxidation treatment condition may also be 41 The oxidation treatment conditions may be treated at 40°C for 1 to 2 hours in an air atmosphere; the oxidation treatment conditions may be treated at 420°C for 1 to 2 hours in an air atmosphere; the oxidation treatment conditions may be treated at 430°C for 1 to 2 hours in an air atmosphere; the oxidation treatment conditions may be treated at 440°C for 1 to 2 hours in an air atmosphere; the oxidation treatment conditions may be treated at 450°C for 1 to 2 hours in an air atmosphere; wherein the oxidation treatment time range in the oxidation treatment conditions is 1 to 2 hours, which may be any specific value of 1h, 1.1h, 1.3h, 1.5h, 1.7h, 1.9h, and 2h.

[0046] In an embodiment of the present invention, the conductive polymer is one of polyaniline, polypyrrole and polythiophene.

[0047] In the embodiment of the present invention, the stirring is to fully contact the base carbon material with the monomers of the monomer solution of the base carbon material and the conductive polymer, promote the chemical grafting reaction of the monomers of the conductive polymer on the surface of the oxidized base carbon material, promote the wrapping of the conductive polymer on the oxidized base carbon material, and improve the bonding force between the two;

[0048] Illustratively, in an embodiment of the present invention, the stirring time is 1 to 4 hours.

[0049] In certain embodiments of the present invention, the conductive polymer is polyaniline, the monomer solution of the conductive polymer is aniline hydrochloride solution, and the reaction accelerator solution is ammonium persulfate hydrochloride solution.

[0050] Preferably, the concentration of the aniline hydrochloride solution is 0.05-0.2M, and the concentration of the ammonium hydrochloride persulfate solution is 0.05-0.2M.

[0051] Specifically, the specific value of the concentration of the aniline hydrochloride solution is any one of 0.05M, 0.1M, 0.15M, and 0.2M; the specific value of the concentration of the ammonium persulfate hydrochloride solution is any one of 0.05M, 0.1M, 0.15M, and 0.2M.

[0052] In certain embodiments of the present invention, the conductive polymer is polypyrrole, the monomer solution of the conductive polymer is a pyrrole monomer hydrochloric acid solution, and the reaction accelerator solution is an ammonium persulfate hydrochloric acid solution.

[0053] In certain embodiments of the present invention, the conductive polymer is polyethylene dioxythiophene in polythiophene, the monomer solution of the conductive polymer is 3,4-ethylene dioxythiophene ether solution, the reaction accelerator solution is ammonium persulfate ether solution, and the ether solution of 3,4-ethylene dioxythiophene contains ferric chloride.

[0054] In the embodiment of the present invention, the carbonization process is specifically performed as follows:

[0055] The obtained substrate wrapped with the conductive polymer is placed at the upwind port of a tube furnace 0 to 15 cm away from the heating area;

[0056] In an inert atmosphere, the heating zone of the tube furnace is heated to 900-1200°C at 1-10°C / s;

[0057] At the same time, the substrate-wrapped conductive polymer is moved to the heating area within 0 to 5 seconds and carbonized for 5 to 60 seconds;

[0058] Subsequently, the substrate-wrapped conductive polymer is removed from the heating area within 0 to 5 seconds to complete the carbonization treatment, and then cooled in the furnace to obtain a surface carbonized conductive polymer composite electrode;

[0059] The inert atmosphere is high-purity (99.99% by volume) nitrogen, argon, helium, etc., which are well known to those skilled in the art and are not limited in the embodiments of the present invention.

[0060] The above-mentioned carbonization treatment is an ultra-fast carbonization treatment proposed by the present invention. By controlling the placement position, movement time and carbonization treatment time of the substrate-wrapped conductive polymer, the conductive polymer material surface layer within 100 nm is rapidly and uniformly carbonized at high temperature to form a core (conductive polymer)-shell (conductive hard shell (carbon layer wrapped shell)) structure, thereby achieving the wrapping of the conductive polymer by the carbon layer, effectively inhibiting the volume expansion and contraction of the conductive polymer during the cyclic charge and discharge process, and improving the structural stability of the conductive polymer electrode material;

[0061] In addition, the above-mentioned carbonization treatment process is an in-situ carbonization process of the surface of the conductive polymer material, forming a stable organic-carbon heterogeneous interface, and the two are tightly bonded.

[0062] In an embodiment of the present invention, the movement of the substrate-wrapped conductive polymer in the tube furnace is achieved by a sample delivery rod;

[0063] The sample delivery rod is movably connected to the tubular furnace, and an airtight structure is provided at the connection between the sample delivery rod and the tubular furnace;

[0064] One end of the sample delivery rod is placed in the tube furnace, and the other end of the sample delivery rod is located outside the tube furnace;

[0065] The airtight structure is an O-ring or a metal seal.

[0066] Example 1

[0067] Preparation of surface carbonized conductive polymer composite electrode:

[0068] Step A, placing a base carbon material in a tube furnace, and oxidizing it at 400° C. in an air atmosphere for 2 hours, wherein the base carbon material is carbon cloth;

[0069] Step B, immersing the oxidized substrate carbon material in a 0.2M hydrochloric acid aniline solution and stirring for 3 hours, then adding a 0.15M hydrochloric acid ammonium persulfate solution dropwise to the precooled mixture at 0-3°C to carry out an oxidative polymerization reaction of the aniline monomer on the substrate carbon material, reacting for 15 hours under continuous stirring, washing the product with a 0.2M HCl solution and deionized water in an ultrasonic cleaner at a power of 250W for 30 minutes, and drying in an oven at 50-60°C to obtain a substrate-coated conductive polyaniline;

[0070] Step C, placing an alumina crucible containing the substrate-wrapped conductive polyaniline prepared in step B at an upwind position 10 to 12 cm away from a heating area in a high-temperature tube furnace, and heating the heating area from room temperature to 1200° C. at a heating rate of 5° C. / s in an inert atmosphere (high-purity nitrogen); then, the crucible is quickly pushed to the heating area within 0 to 5 seconds through a sample delivery rod built into the furnace tube for ultra-fast carbonization treatment for 60 seconds; then, the crucible is quickly moved out of the heating area within 0 to 5 seconds, and the product is taken out after the tube furnace is cooled to room temperature to obtain a surface carbonized conductive polymer composite electrode.

[0071] Performance Test:

[0072] The substrate-wrapped conductive polyaniline obtained in Example 1 was subjected to microscopic observations using a scanning electron microscope (SEM) and a transmission electron microscope (TEM). The results are as follows: Figure 2-Figure 3 , Figure 2 The SEM image of the substrate wrapped with conductive polyaniline. Figure 3 TEM image of substrate-wrapped conductive polyaniline;

[0073] The surface carbonized conductive polymer composite electrode obtained in Example 1 was subjected to microscopic observation by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results are as follows: Figure 4-Figure 5 , Figure 4 This is the SEM image of the surface carbonized conductive polymer composite electrode. Figure 5 This is the HRTEM (high-resolution transmission electron microscopy) image of the surface carbonized conductive polymer composite electrode;

[0074] The substrate obtained in Example 1 is wrapped with conductive polyaniline (i.e. Figure 6 Carbon cloth / polyaniline in the surface) and carbonized conductive polymer composite electrode (i.e. Figure 6 The carbon cloth / polyaniline@carbon shell in the sample were tested for electrochemical rate performance at a current density of 10 A / g. The results are shown in Figure 6 shown.

[0075] from Figure 2-Figure 3 It can be seen that the surface of the carbon cloth is covered with a wrapping, which proves that the present invention utilizes the base carbon material after oxidation treatment to immerse it in the monomer solution of the conductive polymer, stir it, and then add the reaction accelerator solution at 0-5°C to carry out an oxidative polymerization reaction, thereby successfully achieving the conductive polymer wrapping of the base carbon material.

[0076] from Figure 4 It can be seen that the surface of polyaniline has a carbonization tendency ; from Figure 5It can be seen that the thickness of the carbonized layer on the surface of polyaniline is 1.5nm, 1.5nm, and 2.2nm, which proves that the present invention uses an ultra-fast carbonization treatment process to achieve rapid and uniform carbonization of the surface layer of the conductive polymer material within 100nm at high temperature to form a core (conductive polymer)-shell (conductive hard outer shell (carbon layer wrapped shell)) structure.

[0077] from Figure 6 It can be seen that the capacity decay curve of the surface carbonized conductive polymer composite electrode is relatively gentle in the cyclic charge and discharge test, and its specific capacitance can still maintain 92% of the initial value after 10,000 cycles.

[0078] The specific capacitance of the electrode coated with conductive polyaniline was only 51% of the initial value after 10,000 cycles of charge and discharge test.

[0079] It is illustrated that the stability of the surface carbonized conductive polymer composite electrode obtained in Example 1 is much greater than the stability of the electrode stable on the substrate-wrapped conductive polyaniline, and that the surface carbonized conductive polymer composite electrode obtained in Example 1 has excellent electrode cycle stability.

[0080] Example 2

[0081] Preparation of surface carbonized conductive polymer composite electrode:

[0082] Step A, same as step A in Example 1;

[0083] Step B, immersing the oxidized substrate carbon material in a 0.15M pyrrole monomer hydrochloric acid solution and stirring for 3 hours, then adding a 0.1M hydrochloric acid ammonium persulfate solution dropwise to the pre-cooled mixture at 0-3°C to carry out an oxidative polymerization reaction of the pyrrole monomer on the substrate carbon material, reacting for 15 hours under continuous stirring, washing the product with a 0.2M HCl solution and deionized water in an ultrasonic cleaner at a power of 250W for 30 minutes, and drying in an oven at 50-60°C to obtain a substrate-wrapped conductive polypyrrole;

[0084] Step C is the same as step C in Example 1.

[0085] Example 3

[0086] Preparation of surface carbonized conductive polymer composite electrode:

[0087] Step A, same as step A in Example 1;

[0088] Step B, immersing the oxidized substrate carbon material in a 0.2M 3,4-ethylenedioxythiophene ether solution (containing ferric chloride, the concentration of ferric chloride is 0.15M) and stirring for 4 hours, then adding a 0.15M ammonium persulfate ether solution dropwise to the pre-cooled mixture at 1-3°C to carry out an oxidative polymerization reaction of 3,4-ethylenedioxythiophene on the substrate carbon material, reacting for 15 hours under continuous stirring, washing the product with a 0.2M HCl solution and deionized water in an ultrasonic cleaner at a power of 250W for 30 minutes, and drying in an oven at 50-60°C to obtain a substrate-wrapped conductive polyethylenedioxythiophene;

[0089] Step C is the same as step C in Example 1.

[0090] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a surface carbonized conductive polymer composite electrode, characterized in that: include: The oxidized carbon material is immersed in a monomer solution of a conductive polymer, stirred, and then a reaction accelerator solution is added dropwise at 0 to 5° C. to perform an oxidative polymerization reaction, and after the oxidative polymerization reaction is completed, the oxidized carbon material is washed and dried to obtain a conductive polymer wrapped on the substrate; The obtained substrate wrapped with the conductive polymer is carbonized in an inert atmosphere. After the carbonization is completed, a surface carbonized conductive polymer composite electrode is obtained.

2. The method for preparing a surface carbonized conductive polymer composite electrode according to claim 1, characterized in that: The base carbon material includes one of carbon fiber, carbon cloth and graphite paper.

3. The method for preparing a surface carbonized conductive polymer composite electrode according to claim 1, characterized in that: The oxidation treatment condition is 350-450° C. in an air atmosphere for 1-2 hours.

4. The method for preparing a surface carbonized conductive polymer composite electrode according to claim 1, characterized in that: The conductive polymer is one of polyaniline, polypyrrole and polythiophene.

5. The method for preparing a surface carbonized conductive polymer composite electrode according to claim 4, characterized in that: The conductive polymer is polyaniline, the monomer solution of the conductive polymer is aniline hydrochloride solution, and the reaction accelerator solution is ammonium persulfate hydrochloride solution.

6. The method for preparing a surface carbonized conductive polymer composite electrode according to claim 4, characterized in that: The conductive polymer is polypyrrole, the monomer solution of the conductive polymer is a pyrrole monomer hydrochloric acid solution, and the reaction accelerator solution is an ammonium hydrochloride persulfate solution; the conductive polymer is polyethylene dioxythiophene, the monomer solution of the conductive polymer is an ether solution of 3,4-ethylene dioxythiophene, and the reaction accelerator solution is an ammonium persulfate ether solution, wherein the ether solution of 3,4-ethylene dioxythiophene contains ferric chloride.

7. A method for preparing a surface carbonized conductive polymer composite electrode according to any one of claims 1 to 6, characterized in that: The specific operation of the carbonization treatment is as follows: The obtained substrate wrapped with the conductive polymer is placed at the upwind port of a tube furnace 0 to 15 cm away from the heating area; In an inert atmosphere, the heating zone of the tube furnace is heated to 900-1200°C at 1-10°C / s; At the same time, the substrate-wrapped conductive polymer is moved to the heating area within 0 to 5 seconds and carbonized for 5 to 60 seconds; Subsequently, the substrate-wrapped conductive polymer is removed from the heating area within 0 to 5 seconds to complete the carbonization treatment, and then cooled in the furnace to obtain a surface carbonized conductive polymer composite electrode.

8. The method for preparing a surface carbonized conductive polymer composite electrode according to claim 7, characterized in that: The movement of the substrate-wrapped conductive polymer in the tube furnace is achieved by a sample delivery rod; The sample delivery rod is movably connected to the tubular furnace, and an airtight structure is provided at the connection between the sample delivery rod and the tubular furnace; One end of the sample delivery rod is placed in the tube furnace, and the other end of the sample delivery rod is located outside the tube furnace.

9. The method for preparing a surface carbonized conductive polymer composite electrode according to claim 8, characterized in that: The airtight structure is an O-ring or a metal seal.

10. A surface carbonized conductive polymer composite electrode, characterized in that: The conductive polymer is prepared by the preparation method described in any one of claims 1 to 9, and comprises a carbon material substrate, a conductive polymer wrapped on the surface of the carbon material substrate, and a carbide on the surface of the conductive polymer.